Controllable Spin‐Split Phantom Scars in Quantum Dots. Issue 3 (12th January 2023) - Berger, Michael; Berakdar, Jamal
Abstract: Quantum states of systems with an underlying classical chaotic dynamics can be "scarred, " meaning that the associated probability density is localized around the short, unstable periodic orbits. Here, it is shown that, via tunneling, the scarred state can be imaged to a region that does not support scarring. This "phantom scar" is also present in the spin channel and has marked influence on the spin‐dependent system dynamics, as illustrated by explicit calculations for the fidelity and correlation functions. Numerical simulations and analysis are performed for the spin‐dependent electron dynamics in semiconductor‐based double quantum dots, including disorder, Rashba‐type spin‐orbital coupling, exchange fields, and external magnetic fields. The results elucidate the unique feature of scarring as a coherent phenomenon spanning the whole system and affecting its localization properties in a narrow spectral window. Abstract : Impurities in a quantum dot can induce enhanced localization (scars) of electronic density, which affects physical observables. Such scars are found to be teleportable coherently and in a spin‐resolved way via tunneling to another region in space where a second, otherwise unscarred, impurity‐free quantum dot resides, influencing in a nonlocal way and nondestructively the measurement outcome of the impurity‐free quantum dot.